Dynamic simulation of ship fender structure anti-collision - Yi HU; Shifeng DING; Li ZHOU; Wenqian BAO; Ligang ZHAO (Zhongguo Jianchuan Yanjiu, 2022)
Objectives This study aims to investigate the dynamic coupling effect of "hull-fender-dock" during ship berthing.MethodsUsing the nonlinear finite element method, a port side and fender structure finite element model is established to simulate the dynamic evolution of speed, stress and energy during ship berthing. ResultsThe results show that when the fender makes contact with the dock, the ship's speed decreases to zero and the dynamic deformation and interaction force of the fender structure are at their maximum. When the ship is berthing, the fender shows strong energy absorption capacity, accounting for about 70% of the initial total kinetic energy of the ship, and the hull structure is well protected.ConclusionsFurther analysis indicates that, with the improvement of the initial berthing speed, port protection efficiency shows a decreasing trend. The ultimate berthing speed of the target ship of this study is 2.5 kn, and the recommended safe berthing speed is 2 kn. The results of this study can be used as a reference for ship berthing speed limits and hull structure energy absorption design.